Pengaruh Beban Pajak Tangguhan Dan Perencanaan Pajak Terhadap Praktik Manajemen Laba Pada Perusahaan Manufaktur Yang Terdaftar Di Bursa Efek Indonesia Tahun 2014-2018 - Naufal Anis Hilmy; Sudradjat Sudradjat (Jurusan Akuntansi Politeknik Negeri Bandung, 2020)
This study aims to analyze the effect of deferred tax expense and tax planning on earnings management practices in manufacturing companies listed in the Indonesia Stock Exchange for the periode 2014-2018 with firm size as a control variable. This type of research is quantitative research using secondary data from annual financial reports from manufacturing companies listed on the Indonesia Stock Exchange in 2014-2018. The sampling technique uses purposive sampling method. So the sample in this study amounted to 35 companies with observations on 127 financial statements that meet the criteria for observation. The variables studied were deferred tax expense (X1), tax planning (X2), earnings management (Y) and added firm size as a control variable (X3). Data analysis techniques used multiple regression analysis and performed statistical analysis using the help of the IBM SPSS 24 application. The research results partially showed that the deferred tax expense has a significant positive effect on earnings management practices, but tax planning has no significant effect on management practices. While simultaneously, deferred tax expense, tax planning and company size as a control variable have a significant effect on earnings management practices.